Serum amyloid A concentrations, COVID-19 severity and mortality: An updated systematic review and meta-analysis. (April 2021) - Zinellu, Angelo; Paliogiannis, Panagiotis; Carru, Ciriaco; Mangoni, Arduino A.
Highlights: Specific acute phase reactants might be useful for risk stratification in patients with COVID-19. We conducted a systematic review and meta-analysis of studies of serum amyloid A (SAA) in patients with COVID-19. SAA concentrations were significantly higher in COVID-19 patients with severe disease and non-survivors. SAA might assist with risk stratification and monitoring in this group. Abstract: Background and objectives: An excessive inflammatory response in patients with coronavirus disease 2019 (COVID-19) is associated with high disease severity and mortality. Specific acute phase reactants might be useful for risk stratification. A systematic review and meta-analysis was conducted of studies on serum amyloid A (SAA) in patients with COVID-19. Methods: The PubMed, Web of Science, and Scopus databases were searched, covering the period January 2020 to December 2020, for studies reporting SAA concentrations, COVID-19 severity, and survival status. Results: Nineteen studies involving 5617 COVID-19 patients were included in the meta-analysis. Pooled results showed that SAA concentrations were significantly higher in patients with severe disease and non-survivors (standard mean difference (SMD) 1.20, 95% confidence interval 0.91–1.49, P < 0.001). Extreme between-study heterogeneity was observed ( I 2 = 92.4%, P < 0.001). In the sensitivity analysis, the effect size was not significantly affected when each study was removed in turn (range 1.10–1.29). The Begg test ( P = 0.030), but not the Egger test ( P = 0.385), revealed the presence of publication bias. Pooled SMD values were significantly and positively associated with sex ( t = 2.20, P = 0.047) and aspartate aminotransferase ( t = 3.44, P = 0.014). Conclusions: SAA concentrations were significantly and positively associated with higher COVID-19 severity and mortality. This acute phase reactant might assist with risk stratification and monitoring in this group.